2017
DOI: 10.1016/j.disc.2017.03.022
|View full text |Cite
|
Sign up to set email alerts
|

A new labeling construction from theh-product

Abstract: The ⊗ h -product that refers the title was introduced in 2008 as a generalization of the Kronecker product of digraphs. Many relations among labelings have been obtained since then, always using as a second factor a family of super edge-magic graphs with equal order and size. In this paper, we introduce a new labeling construction by changing the role of the factors. Using this new construction the range of applications grows up considerably. In particular, we can increase the information about magic sums of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…All the results in the literature involving the ⊗ h -product had super edge-magic labeled digraphs in the second factor of the product. However, in [14] it was shown that other labeled (di)graphs can be used in order to enlarge the results obtained, showing that the ⊗ h -product is a very powerful tool. Next, we introduce the family T q σ of edge-magic labeled digraphs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…All the results in the literature involving the ⊗ h -product had super edge-magic labeled digraphs in the second factor of the product. However, in [14] it was shown that other labeled (di)graphs can be used in order to enlarge the results obtained, showing that the ⊗ h -product is a very powerful tool. Next, we introduce the family T q σ of edge-magic labeled digraphs.…”
Section: Introductionmentioning
confidence: 99%
“…An edge-magic labeled digraph F is in T q σ if V (F ) = V , |E(F )| = q and the magic sum of the edge-magic labeling is equal to σ. Theorem 1.2. [14] Let D ∈ S k n and let h be any function h : E(D) → T q σ . Then D ⊗ h T q σ admits an edge-magic labeling with valence (p + q)(k…”
Section: Introductionmentioning
confidence: 99%